Sociology of Disaster in the Fulfillment of Adequate Food and Nutrition for Rural Households during Pandemic - Dian Pratiwi Pribadi (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2023)
The fulfllment of adequate food and nutrition had become a challenge during Covid-19 pandemic, particularly at family level in rural area. Prior to pandemic, rural people has suffered from hunger and malnutrition at a high number, and this was increasing because of pandemic. The rising of main food price due to extreme weather and various barriers in food production and distribution are several effects of pandemic in food issue. This action research in the form of a socialization in terms of a community service activity was held to deepen an understanding on the importance of adequate food and nutrition fulfilment at family level and explore alternatives to the food and nutrition fulfilment at public level during Covid-19 pandemic. This research is a participatory action research and is completed by involving the research object in conducting the research, the learning, and the application of the action. As a result, a local agricultural system is acceptable as an alternative to a conventional system in order to deal with food issues, because it can empower the potency of locally natural and human resources to meet the local community’s food demand. By this socialization event, it has formulated an action plan in the form of a series of activities related to a self-sufficient farming based on local resources.